2013
DOI: 10.1007/s40368-013-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting clinical outcome following treatment of early childhood caries under general anaesthesia: a two-year follow-up

Abstract: Despite the high rate of post-operative caries recurrence, DGA is still an acceptable treatment option as it minimises the need for future dental treatment. Compliance by caregivers with post-operative care plans is as important as the procedure itself. In Saudi Arabia, targeting the actual caregivers with post-operative dental health education presents challenges that might affect the clinical outcome of DGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 9 publications
4
25
5
Order By: Relevance
“…The relapse rate in the present study was lower than previously reported. The 6 months relapse in our study was only 1.6 % compared to (Amin et al 2010;El Batawi 2014). Only 2.9 % of children had a previous dental GA in the present study compared to 17 % reported by Almeida et al (2000).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The relapse rate in the present study was lower than previously reported. The 6 months relapse in our study was only 1.6 % compared to (Amin et al 2010;El Batawi 2014). Only 2.9 % of children had a previous dental GA in the present study compared to 17 % reported by Almeida et al (2000).…”
Section: Discussioncontrasting
confidence: 75%
“…Amin et al (2010) reported a 22 % relapse rate in patients attending a recall appointment within 1 year following surgery compared with a 51 % relapse rate in the group attending their first recalls at 13-24 months post-surgery. An increased relapse rate from 51 % in high attendance patients to 68 % in patients with a lower attendance rate was reported by El Batawi (2014). A higher relapse rate was also observed in patients who did not attend immediate follow-up appointments (Foster et al 2006).…”
Section: Discussionmentioning
confidence: 87%
“…A limitation in our study might be our patient record-based data, as in many other studies [ 14 , 16 , 17 , 20 ]. In general, the records can be taken as reliable, because there are statutory rules for the recording and treatment codes used in patient records in Finland.…”
Section: Discussionmentioning
confidence: 99%
“…The compliance of generally healthy children in attending the postoperative review visit scheduled two weeks after comprehensive treatment under DGA has been reported to vary between 48–100%, while the compliance in attending the subsequent recalls has tended to decline over time [ 14 – 17 ]. Caries relapse has been found in 37–54% of those returning to 4–6-month recalls [ 18 , 19 ], and in 53–79% of those returning to recalls within two years [ 14 , 17 , 20 ], a proportion of them again needing treatment under DGA [ 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Buffalo, USA in 2000 reported low rates (39%) of children returning for their immediate follow-up appointment [16]. A recent study in Saudi Arabia reported lower percentages (14%) of patients complying fully with the post-operative recall schedule [17]. Factors contributing to GA review rates are likely to include: cultural [17], socio-demographic, socio-economic and some patients may perceive the appointment as being unnecessary if they have not experienced any adverse effects from the dental GA treatment.…”
Section: Discussionmentioning
confidence: 99%